Training Students' Science Literacy on Biotechnology Using Science, Environmental, Technology, Society (SETS) Visioned Learning Instructional - Zephisius Rudiyanto Eso Ntelok; Ni Wayan Putri Resnasari; Yohannes Marryono Jamun (Universitas Pahlawan Tuanku Tambusai, 2022)
The aim of this research is to develop science learning instructional based on Science Environment Society Technology (SETS) approach which is faceable to facilitate students science literacy. Science learning instructional that developed in this research are lesson plans, student teaching materials, students worksheets and scientific literacy instruments. The method used in this study is the research and development (RnD) using the Dick and Carey model and it was tested to ninth grade students of SMP Negeri 4 Langke Rembong on second semester of 2021/2022 Academic Year. Data were collected using expert validation, observation and test methods. Data were analyzed descriptively quantitative and qualitative. The results of the research show that 1) the science learning instructional developed was valid after being validated by two science teachers and two science lecturers, 2) the practicality of the learning device was obtained from the implementation of the lesson plan in the very good category, 3) the effectiveness of the device was demonstrated by increasing scores and levels scientific literacy with moderate n-gain and student responses to devices and learning implementation are interesting and easy to learn. Based on these results, it can be concluded that science learning instructional based on SETS approach are suitable for practicing student scientific literacy